2013
DOI: 10.1037/a0031689
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of program performance on the Examination for Professional Practice in Psychology (EPPP).

Abstract: Passing the Examination for Professional Practice in Psychology (EPPP) is a prerequisite to professional licensure throughout the United States and much of Canada. As such, the EPPP helps serve a gatekeeping function for the many subspecialties of professional psychology. After first reviewing the history, validation process, known associations with other variables, and criticisms of the EPPP, we summarize the most recent program-level data according to degree type and specialty. To assess the predictors of EP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 23 publications
2
14
0
Order By: Relevance
“…In those studies, both quantitative (Yu et al, 1997) and verbal (Callahan, Ruggero, & Parent, 2013) GRE scores obtained prior to doctoral training have been found to be predictive of subsequent EPPP scores. Sharpless and Barber (2013) also reported that GRE scores, including the advanced psychology test, were predictive of EPPP scores. However, they also found a significant inverse correlation between EPPP scores within programs and the prevalence of diverse students in those same programs.…”
Section: Admissionsmentioning
confidence: 96%
“…In those studies, both quantitative (Yu et al, 1997) and verbal (Callahan, Ruggero, & Parent, 2013) GRE scores obtained prior to doctoral training have been found to be predictive of subsequent EPPP scores. Sharpless and Barber (2013) also reported that GRE scores, including the advanced psychology test, were predictive of EPPP scores. However, they also found a significant inverse correlation between EPPP scores within programs and the prevalence of diverse students in those same programs.…”
Section: Admissionsmentioning
confidence: 96%
“…Despite the small effect size, this difference in pass rate appears to be practically meaningful for graduates of professional psychology programs. Previous studies demonstrated significant correlations between EPPP scores, performance on other standardized tests (e.g., the GRE as in Sharpless & Barber, 2013), and other indications of program competitiveness (e.g., acceptance rates; internship match rates). Interestingly, the programs that ostensibly have the strongest focus on the practice of professional psychology (i.e., PsyDs) appear to perform significantly worse on the EPPP than the more research-oriented PhD programs.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it could be a very promising—and perhaps unique—adjunct to the current licensure process. However, unless the EPPP Part 2 displays real-world evidence of validity and rests upon a firm psychometric footing, it remains vulnerable to the same criticisms levied at the original EPPP (e.g., see Ryan & Chan, 1999; Sharpless & Barber, 2009, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical programs are primarily housed within departments of psychology, whereas counseling programs are located mostly in colleges of education and less often in departments of psychology (Blustein et al, 2005). Clinical PhD recipients score significantly higher on the EPPP licensure exam than counseling psychology PhDs, but only higher than those who graduate from programs housed within departments of education (Graham & Kim, 2011;Sharpless & Barber, 2013).…”
Section: Salient Differences Program Characteristicsmentioning
confidence: 99%